Remoção de sementes artificiais por formigas no entorno de um reservatório hidrelétrico - Silva, Graziele Santiago da (2015)
In Brazil, the electrical power may be produced in different ways and the hydroelectric power stations are the energy matrix of the country. Despite the benefits, they affect ecosystems where they are based since its implementation through its removal. Although hydroelectric stations are the most used sources to produce energy in Brazil, the process of dam decommissioning is unusual in the country for disabled plants. In this sense, it is important to evaluate the banks of the river before the process of dam removal, since the fauna and the flora around it may be directly affected by changes caused during dam removal. Thus, ants involved in ecological roles such as seed dispersion may be used to measure the environmental impacts. Therefore, the present work aimed to assess the seed removal rate by ants around a hydroelectric reservoir in Northern Minas Gerais in order to assist in formulating a recovery plan for reservoir areas after the eventual removal of the dam. Our results showed neither significant differences regarding species richness nor the seed removal rate among studied areas. Only the environmental variable of ground cover percentage by herbaceous plants has been positively related to the seed removal rate. Thus, we suggest recovering a reservoir after decommissioning mainly with plant structures comprising herbaceous plants. Likewise, the characteristics of vegetation transition presented by the region should be maintained in order to provide a better support for the autonomous maintenance of the environment through the process of seed removal performed by ants.